Applying the harmonic plus noise model in concatenative speech synthesis. - Stylianou, Y.
This paper describes the application of the harmonic plus noise model (HNM) for concatenative text-to-speech (TTS) synthesis. In the context of HNM, speech signals are represented as a time-varying harmonic component plus a modulated noise component. The decomposition of a speech signal into these two components allows for more natural-sounding modifications of the signal (e.g., by using different and better adapted schemes to modify each component). The parametric representation of speech using HNM provides a straightforward way of smoothing discontinuities of acoustic units around concatenation points. Formal listening tests have shown that HNM provides high-quality speech synthesis while outperforming other models for synthesis (e.g., TD-PSOLA) in intelligibility, naturalness, and pleasantness
Keywords: Acoustic units; Adapted schemes; Concatenative text-to-speech synthesis; Discontinuities smoothing; Formal listening tests; Harmonic plus noise model; High-quality speech synthesis; Modulated noise component; Natural-sounding signal modifications; Parametric speech representation; Speech intelligibility; Speech naturalness; Speech pleasantness; Speech signal decomposition; Speech signals representation; Time-varying harmonic component